Discerning a ‘Rhetorics of Catechesis’ in Origen of Alexandria’s Commentary on the Gospel of John: A Sociorhetorical Analysis of Book XIII:3-42 (John 4:13-15). - Beyrouti, Francois Elias (Université Saint-Paul / Saint Paul University, 2013)
In this thesis I analyze Origen of Alexandria’s Commentary on the Gospel of John, book IV, paragraphs 3-42 which treats John 4:13-15. I use the tools developed by Sociorhetorical analysis as they provide a systematic approach to studying early Christian texts. Sociorhetorical analysis was first conceived by Vernon K. Robbins and continues to be developed by a group of international scholars under his direction. This methodological tool has been primarily used on Biblical texts, and this thesis is the first to use Sociorhetorical analysis on an early Christian text. I chose Origen because he is the most prominent pre-Nicene theologian and his reputation as a thoroughly Biblical exegete remains until today. Furthermore, he has influenced the greatest Christian Theologians throughout the centuries yet he is frequently misunderstood. Writings on Origen are often passionate, yet very few go beyond a surface analysis. This has resulted in a great deal of discussion about Origen, but very little agreement as to what he is doing. This is the primary problem that I wish to address. We should be intrigued by the various responses that people have had to Origen throughout history. He was a genius, greatly influential on the formation of Christian theology, has remained prominent, but is still seen as an enigmatic figure. My goal is to go beyond the many contradictory statements about Origen by focusing on the rich structure behind his genius. In the first part of the thesis I highlight the praise that Gregory Thaumaturgus, Eusebius, Jerome, Augustine, and the Cappadocians bestow on Origen, and also discuss the controversy that surrounded him throughout his life and the years that followed. However, despite the intensity of this praise and criticism I also show that both camps do not provide adequate structural reasons for their positions. Their assessments indicate that we need a way out of this like-dislike bind in order to move more towards appreciating his writings based on their inner structure and any discernible consistent system. Most authors who have written about Origen’s approach to interpreting Scripture have depended on or begun with On First Principles IV, where he presents the analogy of body, soul, spirit to discuss the different aspects of reading and applying Scripture. The literature on this field is immense. My focus was more specifically on the authors who have written on ComJn. These have all taken different approaches depending on their particular goals and perceptions. Some look for the tripartite division in ComJn, but are disappointed as they can usually only find, at most, two levels. Others have looked for a variety of themes in ComJn such as inspiration, the relationship between the two testaments, or the Holy Spirit. Some have focused on the apologetic elements in ComJn and how it responds to Heracleon. These are all important aspects and most come out in the analysis that I did. However, what these studies do not do and what I show is the integral relationship between these two levels. Though many authors see two or three levels operating within the works of Origen, they rarely discuss the connection between these two levels and how, if there are two, one builds upon the other, and if there are three, the third builds on the first and the second in a progressive manner with a catechetical goal. This is an important contribution at two levels. First, it dispels the notion that Origen was somehow disconnected from the historical sense. Second, the systematic nature of Origen’s writings that comes out with the detailed analysis shows that Origen was not random in his approach. Rather, he proceeded with a specific catechetical intention that moved from looking at the details of the text to an effort at challenging the reader. I would not have been able to make these observations had I not done the analysis using Sociorhetorical analysis’s inner texture, intertexture, and ideological texture. This systematic approach has allowed me to see that in a precisely targeted section in his ComJn there is a definite, well thought out, and repeated pattern which consists of the following points: (1) There are two levels of reality; (2) The first level is important; (3) Remaining at the first level is insufficient; (4) There are advantages of the second level; (5) The second level is reached through dialogue. Without the various levels of the research that I present here, these conclusions could not have been reached. Thus, it is no surprise that within the ocean of research on Origen, this study may appear like a drop -- but hopefully, will be valued as a significant one. Sociorhetorical analysis enabled me to look at this text from a variety of angles in order to get a more complete picture of its structure and goal. I began with inner texture, indexed and charted all the words in ComJn XIII.3-42, then went on to identify the main topics within the text. These findings provided crucial insights in the next level of analysis which focused on how Origen incorporated intertextural elements into his work. Then finally, in the ideological texture section, I dissected the fuller implications of these findings to show the various connections that Origen makes within the limits of the text, with other texts, then finally with the people reading the text. Sociorhetorical analysis enabled me to discover the rich dynamics within which Origen works. This has resulted in placing me firmly on the side of his admirers, but more importantly has provided the rich foundation for which this appreciation can be thoroughly justified.
Keywords: Origen of Alexandria; Rhetoric; Rhetorics of Catechesis; Bible; Interpretation; Sociorhetorical Analysis; Francois E. Beyrouti; Vernon K. Robbins; John 4:13-15; Commentary on the Gospel of John; L. Gregory Bloomquist; Normand Bonneau; Andriy Chirovsky; Harry Maier; Scripture; Early Christianity; Early Christian; Heresy; Orthodoxy; Allegory; Literal; Gospel of John; Commentary; Gregory Thaumaturgus; Eusebius; Saint Jerome; Saint Augustine of Hippo; The Cappadocians; Saint Gregory of Nazianzus; Saint Gregory the Theologian; Saint Basil the Great; Saint Gregory of Nyssa; Karen Jo Torgesen; Ronald E. Heine; Cécile Blanc; Cecile Blanc; Raymond Brady Williams; Jean-Michel Poffet; Henri Crouzel; Michihiko Kuyama; John Anthony McGuckin; Opening - Middle - Closing Texture; Repetitive Texture; Progressive Texture; Narrational Texture; Argumentative Texture; Sensory-Aesthetic Texture; Intertexture; Oral-Scribal Intertexture; Oral - Scribal Intertexture; Cultural Intertexture; Social Intertexture; Historical Intertexture; Ambrose; Patron; Ideological Texture; Ideology; Inner Texture; Author, Text, Reader; Author; Text; Reader; Samaritan Woman; Samaritans; Jesus; Saint Paul University; The University of Ottawa; Emory University; Heracleon; Gnostics; Catechesis; Catechetical; Typology; Jacob; The Well